Dinâmica costeira no entorno do terminal portuário do pecém: estudo de caso no sistema de modelagem costeira do Brasil - Rodrigues, Linara Ivina de Castro (2022)
The present work presents the use of a computational tool applied to a beach in the state of Ceará to understand and analyze the beach's coastal dynamics and, from the results of the research available for the area, with data collected in situ, to prove the usefulness of the tool and its database. Coastal areas are constantly changing, caused by natural events or human activities. In Brazil, where phenomena such as the occupation of the coastal zone generate serious impacts on these environments, the study and knowledge of these spaces are essential to develop appropriate planning for adequate occupation. However, part of this study is hampered by the lack of data to perform these characterizations. Tools with reanalysis databases come in as an alternative to this deficiency. For this work, the tools of the Brazilian Coastal Modeling System (SMC-Brasil) were applied in Praia do Pecém, municipality of São Gonçalo do Amarante, state of Ceará. The first part of the methodology focused on the pre-processing of the SMC-Brasil database. In the second part, during the post-process steps, the propagated cases throughout the domain of the studied area were obtained followed by reconstruction of the series of sea states at any point in the domain. Finally, the wave breaking point in the profile and the longitudinal transport of sediments were estimated. Among the results, the predominance of waves incidence directions for the area was from NE to ESE. The most frequent mean values of wave height ranged from 1.3 m to 1.5 m and peak period around 8 s. The sea and swell wave patterns for the area were well characterized in the results, in general the sea waves arrive from the directions 080º Az to 120º Az, and the swells from 020º Az to 060º Az. The propagation results show, for the most part, a response of the hydrodynamic agents along with the port structure and the Pecém headland. The average longitudinal transport of sediments is in agreement with the coastal drift with a resultant from east to west and an estimated value of approximately 115,000 m³/year. The wave climate for the region, the modeling of wave and current propagation and the sediment transport obtained through the wave reanalysis data from the SMC-Brazil largely coincided with the results collected in the literature, from in situ measurements. The use of the SMC-Brazil proved to be a good tool to assist in the initial understanding of coastal processes, being easy to use and with a large number of resources in a single software.